Outer membrane vesicles of Dinoroseobacter shibae transport a volatile aldehyde - Koteska, Diana; Wang, Hui; Wagner-Döbler, Irene; Schulz, Stefan (Frontiers in Ecology and Evolution, 2023)
Outer Membrane Vesicles (OMVs) of the Gram-negative marine bacterium Dinoroseobacter shibae, a member of the Roseobacteraceae, were investigated for the presence of volatile organic compounds (VOCs). Extracts of vesicles were analyzed by gas chromatography/mass spectrometry (GC/MS). In these analyses the short fatty acid (Z)-5-dodecenoic acid (1) and the related, more volatile aldehyde (Z)-5-dodecenal (8) were identified as VOCs of the OMVs. The aldehyde 8 has not yet been reported before from bacteria. Due to their possible function as signaling molecules, both compounds were tested for Quorum Sensing (QS) inhibition in a bioassay against the QS sensor strain Pseudomonas putida F117 (pKRC12) responsive to long-chain N-acylhomoserine lactones, the effectors of the sensor. Both compounds showed QS inhibitory activity. The potential function of VOCs in OMVs which has not been observed previously is discussed.